2022
DOI: 10.1111/aman.13776
|View full text |Cite
|
Sign up to set email alerts
|

Energizing partnerships in research‐to‐policy projects

Abstract: On the ground, how can research initiatives unfold to make meaningful contributions to real-world practice and real-time policy? This article draws on a case study evaluating an innovative program to alleviate toxic stress, boost resilience, and promote social inclusion among Syrian refugee and Jordanian nonrefugee youth. I describe the kind of project design and community engagement that animates research on stress biology and lived experiences, connecting people with humanitarian practice and policy. I highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 80 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…These findings suggest that stress‐induced poor sleep quality may have contributed to the dramatic rise in mental health issues observed during the COVID‐19 lockdowns. Moreover, this work showcases the critical role that human biologists can play in addressing disparities in global mental health outcomes (Kim, 2020; Panter‐Brick, 2022; Patel et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…These findings suggest that stress‐induced poor sleep quality may have contributed to the dramatic rise in mental health issues observed during the COVID‐19 lockdowns. Moreover, this work showcases the critical role that human biologists can play in addressing disparities in global mental health outcomes (Kim, 2020; Panter‐Brick, 2022; Patel et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Our findings also offer an in-depth understanding of why and how stakeholders collaborate, and what works to produce impactful science. Previous analysis of research stakeholder engagement has offered a classification of four types of impact: (1) conceptual (changing knowledge, understanding, and attitudes); (2) instrumental (changing policy and practice, given research findings); (3) capacity-building (changing researchers’ ability to conduct future work), and (4) connectivity (shaping the existence and strengths of networks of people and organizations using the research) [ 37 , 38 ]. In this context, our qualitative and quantitative data provide insight into how the infrastructure and contextual factors of a large longitudinal research consortium produces impact for its stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, it informed approaches to peace and conflict programingthe mindfulness and social inclusion model was folded into broader community-based interventions aimed at preventing violent extremism in youth. In brief, Mercy Corps officers reported that our research had increased their confidence in an empathy-type of youth programing (Elrha, 2023a, Panter-Brick, 2022. The study was selected as a case analysis of humanitarian health research in a collection of Research in Practice articles commissioned by the Fogarty International Center of the U.S. National Institutes of Health (Mistry et al, 2021).…”
Section: Pathways To Resilience and Flourishing In Syrian Communitiesmentioning
confidence: 99%
“…Approaches to network humanitarianism are still relatively new, partly because humanitarian funding priorities are largely focused on addressing emergency needs. Yet calls have been made to secure more dedicated funding for the purpose of enhancing agency, connectivity and social inclusion in crisis settings (see Panter-Brick, 2021). In recent years, new forms of humanitarian action have championed a ‘whole-of-society approach’ to work in contexts of forced displacement.…”
Section: Three Key Frames Of Humanitarian Workmentioning
confidence: 99%